2023
DOI: 10.1142/s0218126623503061
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis and EEG Signal Filtering Using Design of Window Function Based on Optimization Methods

Abstract: The window functions, which are widely used in Finite Impulse Response (FIR) digital filter design with the Fourier Series Methods, aim to eliminate the oscillations adversely affecting the filter performance that occur during the filter design. Window functions, which were developed with different methods in the literature, were designed with three different optimization techniques in this study. By using Particle Swarm Optimization (PSO), Grey Wolf Colony Optimization (GWCO), Cuckoo Search Optimization (CSO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…As a result of the filter spectral analysis for N = 51 and N = 101, it is observed that the filters designed based on Cosh-Hamming and Cosh-Von Hann windows can provide better results than filters designed with other windows. The proposed windows can also be used in applications such as communication [37][38][39], image processing [40,41] and biomedical processing [42,43] instead of the Kaiser window and other well-known windows.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the filter spectral analysis for N = 51 and N = 101, it is observed that the filters designed based on Cosh-Hamming and Cosh-Von Hann windows can provide better results than filters designed with other windows. The proposed windows can also be used in applications such as communication [37][38][39], image processing [40,41] and biomedical processing [42,43] instead of the Kaiser window and other well-known windows.…”
Section: Discussionmentioning
confidence: 99%